Dioscin reduces ovariectomy-induced bone loss by enhancing osteoblastogenesis and inhibiting osteoclastogenesis. (June 2016) - Tao, Xufeng; Qi, Yan; Xu, Lina; Yin, Lianhong; Han, Xu; Xu, Youwei; Wang, Changyuan; Sun, Huijun; Peng, Jinyong
Graphical abstract: Abstract: Our previous studies showed that dioscin can promote osteoblasts proliferation and differentiation in vitro, but its anti-osteoporosis effect in vivo and the underlying mechanisms remain unclear. In the present work, the results showed that dioscin significantly increased the viability of MC3T3-E1 cells, ALP level and alizarin red S staining area, markedly decreased the numbers of RANKL-induced TRAP-positive multinucleated cells and bone resorption pits formation, enhanced the levels of some osteogenic markers including COL1A2, ALP and OC, which suggested that dioscin clearly promoted osteoblasts proliferation and suppressed osteoclasts formation. In vivo experiments demonstrated that dioscin obviously reduced OVX-induced body weight increase, and improved the biochemical indexes including ALP, StrACP, OC, DPD/Cr, HOP/Cr, BMD, biomechanics and microarchitecture. Moreover, H&E, TB, TRAP staining, and fluorescent double labeling tests indicated that dioscin enhanced osteoblastogenesis and inhibited osteoclastogenesis. Further researches demonstrated that dioscin promoted osteoblastogenesis through up-regulating OPG/RANKL ratio, and inhibited osteoclastogenesis through down-regulating the levels of RANKL induced TRAF6 and the downstream signal molecules including MAPKs, Akt, NF-κB, AP-1, cathepsin K and NFATc1. In addition, dioscin also inhibited TLR4/MyD88 pathway to decrease the levels of TRAF6 and the related proteins. These findings provide new insights to elucidate the effects of dioscin against OVX-induced bone loss, which should be developed as a potential candidate for treating postmenopausal osteoporosis in the future.